Temperature Management With Paracetamol in Acute Stroke Patients: Evidence From Randomized Controlled Trials - Chen, Huawei; Qian, Hui; Gu, Zhiwei; Wang, Majun (Frontiers in Neurology, 2018)
Whether or not paracetamol can improve functional outcomes in patients with acute stroke has been examined in several clinical trials. The inconsistent results of these trials have caused great controversy regarding the need for further studies. In the present meta-analysis, we aimed to address this controversy. The main databases (Medline, Embase, and Cochrane Library) were searched for randomized controlled trials involving the use of paracetamol in acute stroke patients. Pooled relative risks (RRs) or mean differences (MDs) and 95% confidence intervals (CIs) were calculated using a random-effects model. A total of 1836 patients were pooled from 4 phase II and 2 phase III trials. Paracetamol resulted in a significant reduction in body temperature after 24 h (MD, -0.21; 95% CI, -0.28 to -0.13; P < 0.001) and mortality rate after 7–14 days (RR, 0.62; 95% CI, 0.41-0.93; P = 0.02) compared with the placebo group; however, no effect of paracetamol was observed in the modified Rankin Scale score (RR, 1.07; 95% CI, 0.91-1.27; P = 0.40) or Barthel index score (RR, 0.98; 95% CI, 0.91-1.06; P =0.63) at 30 or 90 days. No significant differences were observed with respect to serious adverse events between the paracetamol and placebo groups (P > 0.05). Subgroup analyses were performed to detect the source of the heterogeneity, which showed that high proportion of patients with ischemic stroke, serious condition at baseline, and late time-to-treatment had an adverse impact on the effect of paracetamol post-stroke. In conclusion, temperature management with paracetamol in acute stroke patients is safe. Although paracetamol reduced the mortality rate in the early stage of stroke, paracetamol did not appear to affect long-term mortality and functional recovery. It should be noted that this conclusion is based on the results from poor quality of the included studies. A large clinical trial with a focus on early treatment of patients with mild stroke is warranted.